Removal of Radionuclides from Fukushima Daiichi Waste Effluents. Issue 2 (3rd April 2019) - Lehto, Jukka; Koivula, Risto; Leinonen, Heikki; Tusa, Esko; Harjula, Risto
Abstract : This paper describes the processes used at the Fukushima Daiichi plant, Japan, to purify the waste effluents generated in the cooling of damaged reactors. These include primary cesium removal with the Kurion zeolite system and the SARRY system utilizing silicotitanate to remove radiocesium from water recirculated to reactors for cooling. Another process is the ALPS system to purify the retentates of the reverse osmosis plant to further purify the water from radionuclides after primary cesium separation. In ALPS, a major role is played by the transition metal hexacyanoferrate product CsTreat and sodium titanate SrTreat in the removal of radiocesium and radiostrontium, respectively. The performance of these four exchangers (zeolite, silicotitanate, hexacyanoferrate, and sodium titanate) is critically analyzed with respect to processing capacities and the decontamination factors obtained in the processes. Furthermore, general information on preparation, structure and ion exchange of these ion-exchanger categories is given with additional information on their use in nuclear waste effluent treatment processes. Finally, the importance of selectivity and associated factors are discussed.